V-057 INTRAPERITONEAL ONLAY MESH (IPOM) TECHNIQUE FOR THE LAPAROSCOPIC TREATMENT OF INGUINAL HERNIA. (13th October 2022) - Bellino, R; Giaccone, M; Sandrucci, S
Abstract: Laparoscopic treatment of inguinal hernia is a widely accepted technique, especially in the case of bilateral or recurrent inguinal hernias. The evolution of materials has led to the successful use of double layer prostheses for the intraperitoneal treatment of wall defects, significantly reducing the mesh-related complications. In this regard, the literature data and the availability of non-absorbable, transparent, light surgical prostheses in polypropylene, composed of a macroporous monofilament mesh and a transparent film, have led to the re-proposal of the IPOM technique also for the treatment of primary inguinal hernias. After the laparoscopic access in the abdomen using a 10 mm trocar in the umbilical region and two 5 mm trocars operating in the Iliac fossae, the hernia is reduced by returning the hernial contents to their original compartments and the hernial sac is closed with the possible lipoma using purse-string suture. Subsequently, a polypropylene composite prosthesis is then inserted into the abdomen, centered on the defect and fixed to the wall by tack and chemical glue. To date we have performed 10 procedures on 6 patients (4 with bilateral hernia). The longest follow-up is one year. The patients were all discharged the day after the surgery, reporting a mean postoperative pain score (assessed with EHS QoL scale) equal to 2 (range: 0–4), and the work resumption after a week in average. This technique, which is easy to perform and reproducible, can significantly reduce operating times and minimize complications related to the preparation of the peritoneal pocket.